Stock Option Plan e incidência previdenciária - Simões, Thiago Taborda (2015)
Stock Options are most used to retrain and retain executives and employees. In the United States, rules on the subject have been around since the 40s. In Brazil , Law 6.404/1976 addressed the issue in a superficial way, and only in late 2008 it appeared that the first specific rule on the subject, with the CPC 10 Share-based payment. This work is founded on the oretical analysis and practice of stock options in the relationship between employer and employee, and the consequent taxation or not through social contribution on the payroll and other labor income. To this end, we will hold the construction of the basis for calculating employer contributions, for reasons of technical and historical nature of stock options until reach the framework of the institute on the basis of calculation of employer contributions